Aulas hospitalarias, formación de profesores y prácticas pedagógicas: aprendizajes para su institucionalización - Albadan-Vargas, Juan Pablo; Castro-Cortes, Claudia Cecilia (Educación y Ciudad, 2023)
This article presents characterizations, learnings, and challenges that were acknowledged during the program of In-Hospital Classrooms of the Education Department of Bogotá city and the internship of education, offered to pre-service teachers, coming into view the systematization of parts of curricular research processes on inclusive education carried out in the Mathematics Teacher Licensure at the Universidad Distrital Francisco José de Caldas -UD-. The reflection seeks to contribute to an evolutive and dynamic comprehension of inclusive education, centered in the accompaniment in mathematics class, of the students undergoing an illness situation. As results, come up reflections on these types of pedagogical interventions as enhancers of diverse sceneries for pre-service teachers initial training in Colombia. Lastly, as a challenge, the need of institutionalizing In-Hospital Classrooms and Hospital Pedagogy is acknowledged as a concretion mechanism of an education, regulatory, and curricular policy that answers to the demand of inclusive education. Thus, avoiding exclusion and marginalization of these students from the education system.